2010
DOI: 10.1038/cddis.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-205 and miR-31 confers resistance to chemotherapy-induced apoptosis in prostate cancer cells

Abstract: Advanced prostate cancers are known to acquire not only invasive capabilities but also significant resistance to chemotherapy-induced apoptosis. To understand how microRNAs (miRNAs) may contribute to prostate cancer resistance to apoptosis, we compared microRNA expression profiles of a benign prostate cancer cell line WPE1-NA22 and a highly malignant WPE1-NB26 cell line (derived from a common lineage). We found that miR-205 and miR-31 are significantly downregulated in WPE1-NB26 cells, as well as in other cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
153
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(169 citation statements)
references
References 29 publications
(29 reference statements)
11
153
0
4
Order By: Relevance
“…15 We noticed two peaks of p63, at a À 13 Kb and þ 2 Kb from the recently identified 16 miR-205 transcriptional start site (TSS; Figure 2a). Search for p63 motifs in these regions highlighted three highly predicted consensus sequences in the former, and two flanking the þ 2 Kb site (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…15 We noticed two peaks of p63, at a À 13 Kb and þ 2 Kb from the recently identified 16 miR-205 transcriptional start site (TSS; Figure 2a). Search for p63 motifs in these regions highlighted three highly predicted consensus sequences in the former, and two flanking the þ 2 Kb site (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence indicates that miRNAs can act as ideal molecular targets for cancer diagnosis, prognosis and therapy in many types of cancers (20)(21)(22). Various miRNAs have been used to detect cancer and to develop miRNA-based therapeutic strategies in PCa (23)(24)(25). To explore different strategies for cancer therapeutics, more studies are needed to identify novel and valuable miRNAs and further, to investigate the role and molecular mechanisms of these miRNAs in PCa tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, considerable evidence has revealed the important roles of miR-31 in cancer, but whether this miRNA functions as a tumor suppressor or an oncogene differs according to cancer type. miR-31 reportedly contributes to apoptosis resistance in PCa cells by targeting the antiapoptotic protein E2F6 29,35 and can antagonize metastasis by suppressing expression levels of ITGA5, RDX and RhoA in breast cancer. 36 Interestingly, our functional analyses showed that restoration of miR-31 in PCa cell lines inhibited cell migration and invasion more significantly than cell proliferation, suggesting that miR-31 may also contribute to cancer invasion and metastasis in PCa.…”
Section: Discussionmentioning
confidence: 99%